Influence of Matching the Processing Delays of Cochlear Implant and Hearing Aid Devices for Bimodal Listeners on Speech Recognition in Noise. - Richter, Margaret E.; Rooth, Meredith A.; Dillon, Margaret T. (American Journal of Audiology, 2024)
Purpose: Cochlear implant (CI) recipients who listen with a hearing aid (HA) in the contralateral ear, known as bimodal listeners, demonstrate individual variability in speech recognition in noise. This variability may be due in part to differences in the processing delays of the CI and HA devices. This study investigated the influence of matching the processing delays of CI and HA devices on masked speech recognition for bimodal listeners. Method: Twelve postlingually deafened adult CI recipients completed a task of masked speech recognition in two listening conditions: (a) independent default CI and HA processing delays (mismatched) and (b) with their HA-specific delay applied to the CI processing delay (matched). Speech recognition was evaluated with AzBio sentences presented in a 10-talker masker at a 0 dB SNR. The target was presented from the front loudspeaker at 0° azimuth, and the masker was co-located with the target, presented 90° toward the CI ear, or presented 90° toward the HA ear. Results: There was a significant main effect for target-to-masker configuration, with better performance when the masker was spatially separated from the target. Better masked speech recognition was observed in the matched condition as compared to the mismatched condition. Conclusion: Bimodal listeners may experience better masked speech recognition when the processing delay of the CI is individualized to match the processing delay of the contralateral HA.